Development of test facilities for thermo-mechanical fatigue testing. (April 2019) - Palmer, J.; Jones, J.; Dyer, A.; Smith, R.; Lancaster, R.; Whittaker, M.
Highlights: Four bespoke TMF test facilities have been developed and evaluated. Trials conclude that different test parameters require a unique mechanical approach. No crack tip heating was found using induction coil systems for TMF CG experiments. Abstract: Thermo-mechanical fatigue data is critical for the generation of appropriate lifing methodologies for a range of in-service applications where non-isothermal conditions are prevalent. Recently the development of more standardised testing approaches through appropriate code of practice documents and international standards has proved crucial. In the current paper, several methods of undertaking TMF testing are explored, with the benefits and pitfalls of each test type investigated. It is shown that bespoke test setups are often required, dependent on material, TMF cycle and specimen type. Further developments are suggested, along with a suggested methodology for TMF crack growth tests.